2018
DOI: 10.18203/2349-2902.isj20181143
|View full text |Cite
|
Sign up to set email alerts
|

Study of factors predicting clinical outcomes of extracorporeal shock wave lithotripsy in Indian patients with upper urinary tract calculi

Abstract: Background: Extracorporeal shock wave lithotripsy (ESWL) is an effective non-invasive method for managing urinary tract calculi. Present study was undertaken to evaluate factors that may influence ESWL clinical outcomes in Indian patients with urinary tract calculi.Methods: This prospective study was conducted at Department of Urology, Medical Trust Hospital Cochin, India in the period from September 2006 to March 2009. Sixty patients with upper urinary tract lithiasis having stone size between 5 to 25 mm were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There have been studies reporting the sex of the patient to be a factor affecting pain behavior, with pain tolerance being higher in males, and reporting that this difference between females and males is a re ection of cultural attitudes towards pain (8). Stone size also in uences the success of ESWL procedures, being low in stones 2 cm or larger (24). A previous study reported that small stones caused more pain during break-up (25).…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies reporting the sex of the patient to be a factor affecting pain behavior, with pain tolerance being higher in males, and reporting that this difference between females and males is a re ection of cultural attitudes towards pain (8). Stone size also in uences the success of ESWL procedures, being low in stones 2 cm or larger (24). A previous study reported that small stones caused more pain during break-up (25).…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies reporting the sex of the patient to be a factor affecting pain behavior, with pain tolerance being higher in males, and reporting that this difference between females and males is a reflection of cultural attitudes towards pain (8). Stone size also influences the success of ESWL procedures, being low in stones 2 cm or larger (24). A previous study reported that small stones caused more pain during break-ups (25).…”
Section: Discussionmentioning
confidence: 99%